PELAKSANAAN HYGIENE SANITASI DEPOT DAN PEMERIKSAAN KANDUNGAN BAKTERI ESCHERICHIA COLI PADA AIR MINUM ISI ULANG DI KECAMATAN TANJUNGPINANG BARAT TAHUN 2012 - Veronica Amelia Simbolon (Lingkungan dan Kesehatan Kerja, 2012)
Sanitize Hygiene Implementation  and Examination of Escherichia Coli Content on Refill Drinking Water Depot on Tanjung Pinang Barat Sub-District in 2012. Water represents one the requirement very important human being. So to peaceful and healthy yielded drinking water hence needed by effort management drinking water depot sanitize hygiene. Contamination of drinking water marked with existence of Escherichia coli bacterium as indicator contamination of water.Intention of this research is to know sanitize hygiene execution and obstetrical inspection of  Escherichia coli in refill drinking water yielded by Town Tanjungpinang West area drinking water depot. Method which is used in this research  to have the character of descriptive seen sanitize hygiene execution and inspection of laboratory to Escherichia coli content in refill drinking water. Technics of intake of sample that is totalizing sampling. Amount of sample which is observation and checked that is 10 refill drinking water depot. Observation conducted in District of Tanjungpinang West. Result of research indicate that entire/all drinking water depot not yet fully applied sanitize hygiene execution for example: location, building, relocation of standard water, desinfeksi, consumer service, employees, lawn, so that result of production some ineligible town Tanjungpinang West area drinking water depot of health. Result of inspection laboratory to positive Escherichia coli content in two drinking water depot ( 20%). Pursuant to that thing, need performing counseling and observation by relevant institution or Public Health service about is important of drinking water depot sanitize hygiene important of refill so that drinking water which consumed by up to standard society of health.